Born to run : a hidden tribe, superathletes, and the greatest race the world has never seen - McDougall, Christopher, 1962- (New York : Alfred A. Knopf, 2009)
McDougall reveals the secrets of the world's greatest distance runners--the Tarahumara Indians of Copper Canyon, Mexico--and how he trained for the challenge of a lifetime: a fifty-mile race through the heart of Tarahumara country pitting the tribe against an odd band of super-athletic Americans.
leisurereading.
Keywords: Running races -- Mexico -- Copper Canyon Region; Tarahumara Indians -- Mexico -- Copper Canyon Region; Long-distance running -- Mexico -- Copper Canyon Region; Long-distance runners -- Mexico -- Copper Canyon Region; Long-distance runners -- United States -- Biography; Running -- Mexico -- Copper Canyon Region; Athletes -- United States